2021
DOI: 10.33448/rsd-v10i9.18022
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias para a melhoria da eficiência do cultivo folicular in vitro: Importância da suplementação do meio e estudo das alterações epigenéticas

Abstract: Considerando o impacto que o estresse oxidativo (EO) e as alterações epigenéticas podem exercer sobre a foliculogênese, o melhor entendimento desses eventos nos auxiliam na busca da melhor eficiência do cultivo in vitro (CIV) de folículos ovarianos em diversas espécies. Diante disso, o objetivo dessa revisão é abordar as principais características e avanços do CIV folicular, expondo as suas limitações (ex. EO e alterações epigenéticas) e alternativas (ex. antioxidantes e meio condicionado de células-tronco mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 126 publications
(123 reference statements)
0
4
0
1
Order By: Relevance
“…During IVFC, suboptimal conditions in the culture environment may alter the methylation pattern (Silva et al, 2022). Thus, assessing the methylation profile during in vivo folliculogenesis (Seneda et al, 2008; Sha, Jiang, et al, 2020) may be a useful marker for the optimization of IVFC conditions (Silva et al, 2021, 2022). In this study, the methylation profiles of H3K4me3 and H3K9me3 were evaluated in PA and EA follicles after in vivo and in vitro conditions, along with the supplementation of anethole during in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During IVFC, suboptimal conditions in the culture environment may alter the methylation pattern (Silva et al, 2022). Thus, assessing the methylation profile during in vivo folliculogenesis (Seneda et al, 2008; Sha, Jiang, et al, 2020) may be a useful marker for the optimization of IVFC conditions (Silva et al, 2021, 2022). In this study, the methylation profiles of H3K4me3 and H3K9me3 were evaluated in PA and EA follicles after in vivo and in vitro conditions, along with the supplementation of anethole during in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…During IVFC, suboptimal conditions in the culture environment may alter the methylation pattern (Silva et al, 2022). Thus, assessing the methylation profile during in vivo folliculogenesis (Seneda et al, 2008;Sha, Jiang, et al, 2020) may be a useful marker for the optimization of IVFC conditions (Silva et al, 2021(Silva et al, , 2022. In this study, the methylation profiles of T A B L E 2 Percentages of morphologically intact, extruded, and degenerated follicles and antrum formation, mean (± SEM) follicular diameters and daily growth rate in vitro of caprine follicles.…”
Section: Ros Levels In the Spent Mediummentioning
confidence: 91%
“…Notably, by coupling the use of eCG with the beneficial effect of FBS-free medium supplementation, the performance of meiotic competence acquisition was similar to that of the oocytes collected from the in vivo EA follicles (75.5% vs. 77.7% MII oocytes, respectively). Accordingly, Park et al demonstrated how the replacement of FBS-supplemented medium with an FBS-free medium exerted a useful effect on oocyte maturation systems, contributing to identifying the functional elements necessary for folliculogenesis [58]. Notably, the use of FBS-free medium supported higher follicular survival rates when compared to the medium supplemented with FBS [56].…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the gathered data, eCG was the treatment that guaranteed the greatest acquisition of meiotic competence under ivF validated conditions, especially in those derived from follicles with a degree of growth higher than or equal to 40%. In order to evaluate whether the eCG's positive influence on in vitro follicle culture was maintained under different cultural conditions, the oFSH and eCG stimulation was further assessed under in vitro follicle culture carried out in an FBS-free medium [56][57][58].…”
Section: Oocyte Meiotic Competence Promoted In Ecg and Ofsh Ivf Grown...mentioning
confidence: 99%
“…As mutações epigenéticas são responsáveis pela causa de alteração na função gênica por meio de mudanças químicas sem alterar o sequenciamento do DNA, moldando a partir do mecanismo da metilação do DNA sendo uma alteração epigenética que ocorre no genoma humano (Silva, et al, 2021).. Esta alteração tem como princípio a adição de um grupo metil na posição C5, ou seja, ao quinto carbono do anel de citosina, sendo assim formando 5-metilcitosina. O processo de metilação, tem um padrão específico de reações de extrema importância para o desenvolvimento humano, que se faz necessário antes e depois do nascimento (Zhang, et al, 2020).…”
Section: Processo De Metilação Do Dnaunclassified